2020
DOI: 10.2139/ssrn.3623146
|View full text |Cite
|
Sign up to set email alerts
|

The Pricing of Green Bonds: Are Financial Institutions Special?

Abstract: The financial system plays a major role in the transition to a low-carbon economy. We investigate this issue analyzing the recent developments and challenges in the bond and debt markets. First, we study the pricing of green bonds at issuance. We find a premium when green bonds are issued by supranational institutions and corporates while there is no effect for financial institutions. We also document an effect for external review and repeated access to this market. Second, we investigate lending decisions by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 13 publications
5
40
1
1
Order By: Relevance
“…Corporate institutions and financial institutions accounted for a plurality of issues in 2019. Investors from several regions declared an excess of demand for green bonds issued, in particular by corporate issuers 8 . In terms of regions, the largest share of issues in 2019 fell to European countries (approximately 45%), followed by the Asian-Oceanian countries, and North America.…”
Section: The Main Trends and Prospects Of Development Of The Green Bomentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate institutions and financial institutions accounted for a plurality of issues in 2019. Investors from several regions declared an excess of demand for green bonds issued, in particular by corporate issuers 8 . In terms of regions, the largest share of issues in 2019 fell to European countries (approximately 45%), followed by the Asian-Oceanian countries, and North America.…”
Section: The Main Trends and Prospects Of Development Of The Green Bomentioning
confidence: 99%
“…Banga J. The green bond market: a potential source of climate finance for developing countries, 2019 8. CBI (2019).…”
mentioning
confidence: 99%
“…Hachenberg and Schiereck (2018) also found that labeled green bonds traded tighter than non-green bonds by the same issuers. Fatica et al (2019) showed, from their panel data regressions, that there was a greenium for green bonds issued by supranational institutions and corporates. Bour (2019) identified the yield discount of green bonds, on average, at 23.2 basis points.…”
Section: Select Literature On Green Bondsmentioning
confidence: 99%
“…Furthermore, green bonds that obtained a CBI certificate showed a discount of around 15 basis points. Fatica et al (2019) showed, from their panel data regressions, there was a greenium for green bonds issued by supranational institutions and corporates. However, there was no effect for green bonds issued by financial institutions.…”
Section: Evidence Of Green Premiummentioning
confidence: 99%
“…They argue that these industries are more exposed to social and environmental risks and, thus, possess a greater need to increase user confidence in the credibility of their reported activities. Similarly, Fatica, Panzica, and Rancan (2019) suggest that for financial institutions, it might be more difficult to mitigate information asymmetry and to signal their environmental commitment to the capital markets. Therefore, I run the regression for the subsample of issuers classified as "Financials" and present the result in column (4) of Table 4.5.…”
Section: The Effect Of Voluntary Disclosurementioning
confidence: 99%